Translating the Untranslatable: The Case of Czech-German and Czech English Code-switching. - Konvička, Martin (Slavia Occidentalis, 2014)
The article offers a new perspective on the phenomenon of code-switching by looking at it from the point of view of translation studies. In doing so, the article addresses the general issue of untranslatability as well. Both theoretical topics are discussed using the example of the German translation of the Czech novel Konec punku v Helsinkách written by Jaroslav Rudiš. The aim of the article is to identify the different compensation strategies used to translate the untranslatable, i.e., the Czech-German and Czech-English code-switching in the novel.